2018
DOI: 10.3390/joitmc4040059
|View full text |Cite
|
Sign up to set email alerts
|

Triggers of Collaborative Innovation in Online User Communities

Abstract: This study contributes to the understanding of collaborative innovation in online user communities. Aside from providing evidence for the existence of these communities, prior research focused on users’ motivations, backgrounds, and roles at the micro level but largely neglected to examine the effects of individual user activities on joint activities at the community level. By applying a netnographic research design, which is followed by a content analysis step and logistic regression analysis, we explore to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 74 publications
(119 reference statements)
0
13
0
Order By: Relevance
“…Open innovation micro-dynamics. Source: [1].Open principles in new business models of information systems, learning patterns in dynamic technological system lifecycles, triggers of collaborative innovation in online user communities, and the transformation from design thinking to artistic thinking are also emerging themes of open innovation micro-dynamics[64][65][66][67].In uncertain markets, new metrics can help companies to play poker as well as chess by managing open innovation[68]. Specifically, databases, case studies, and theoretical research have revealed that SMEs require motivations of open innovation with good control of the increasing complexity from various aspects[17,23,69,70].…”
mentioning
confidence: 99%
“…Open innovation micro-dynamics. Source: [1].Open principles in new business models of information systems, learning patterns in dynamic technological system lifecycles, triggers of collaborative innovation in online user communities, and the transformation from design thinking to artistic thinking are also emerging themes of open innovation micro-dynamics[64][65][66][67].In uncertain markets, new metrics can help companies to play poker as well as chess by managing open innovation[68]. Specifically, databases, case studies, and theoretical research have revealed that SMEs require motivations of open innovation with good control of the increasing complexity from various aspects[17,23,69,70].…”
mentioning
confidence: 99%
“…In contrast to this, various examples exist in which the users had a bigger influence on the innovation process, while innovation processes were also very successful, for example, in online user communities and with regard to smart energy innovations [35][36][37].…”
Section: Research On User Innovationmentioning
confidence: 97%
“…Meanwhile, what can increase consumer satisfaction in addition to products is "delivery service, friendliness, and speed of the seller" [7,8,21,50]. Consumer disappointment has been found to have an impact on offline sales, and it has been determined that consumers trust reviews on the internet [9,67,68]. Thus, OPRs are essential for product development that supports sales strategies [10,14,16,17,51].…”
Section: Managerial Implicationsmentioning
confidence: 99%